Représentations croisées du vin et de l’alcool chez Davodeau et Kundera - Luís Carlos Pimenta Gonçalves (Carnets)
After a brief presentation of the theme of wine and alcohol in (hyper)contemporary literature and comics, this article will focus on the representations of alcohol and wine by the writer Milan Kundera, notably in his penultimate novel L'Ignorance (2000), and in the cartoonist and screenwriter Étienne Davodeau in Les Ignorants, a tale of a cross initiation (2011) where wine and the work of the vine appear as the main themes of this graphic novel.